Seldinger vs modified Seldinger techniques for ultrasound-guided central venous catheterisation in neonates: a randomised controlled trial. (December 2018) - Song, I.-K.; Kim, E.-H.; Lee, J.-H.; Jang, Y.-E.; Kim, H.-S.; Kim, J.-T.
Abstract: Background: Central venous catheterisation in neonates is difficult. The purpose of this study was to compare the Seldinger and modified Seldinger techniques for ultrasound-guided internal jugular vein catheterisation in neonates. Methods: In this randomised, controlled trial, 120 neonates (≤1 month old) requiring central venous catheterisation under general anaesthesia were allocated into either the Seldinger ( n =60) or the modified Seldinger ( n =60) group. The primary outcome was the incidence of successful catheterisation on the first attempt. We also assessed the incidences of successful puncture on the first attempt, successful guide wire insertion on the first attempt, and successful final catheterisation. Results: The primary outcome, the incidence of successful catheterisation on the first attempt was higher in the modified Seldinger group than in the Seldinger group (83% vs 65%; relative risk=1.282; 95% confidence interval, 1.032–1.594; P =0.025). The incidence of successful guide wire insertion on the first attempt was also higher in the modified Seldinger group (95% vs 75%; relative risk=1.267; 95% confidence interval, 1.082–1.482; P =0.003). Other incidences did not differ significantly between the groups. Conclusions: For ultrasound-guided internal jugular vein catheterisation in neonates, the modified Seldinger technique showed superiority over the Seldinger technique in terms of successful catheterisation and guide wire insertion on the first attempt. Clinical trial registration: NCT02688595 .